Impact of Parenting Style on Adolescent Aggressive Behaviour - John, Angel Anu; John, Angel Anu; Sharma, Hariom (International Journal of Psychosocial Rehabilitation, 2020)
The cardinal aim of existing research isto measure the impact of parenting style on aggressive behavior. To reach the objectives of the present study the primary data was collectedof 100 adolescents between the age group 15-19 years (mean age = 15.68) through purposive and convenient sampling methods from Ernakulam District, Kerala. For the assessment procedure Scale of Parenting Style and the Aggression Scale were used. As the research is under process, therefore the obtained primary data will be statistically analyzed through descriptive, inferential and correlation statistics The findings will be discussed on the basis of the literature review. Findings discovered that parenting styles and aggression has no connections, nevertheless when each factor of parenting style is considered the more control the less aggressive the child will be. In other words the more the control is the child will be submissive in nature. Aggression is almost same in boys and girls.